The effect of Tuina based on the concept of hip-knee-ankle conjugation in patients with chronic ankle instability: study protocol for a randomized controlled trial - Wen, Zonglin; Lyu, Ruoyun; Wang, Wei; Hua, Xia; Yu, Yifeng; Zeng, Ke; Kong, Lingjun; Wang, JianWei (Frontiers in Rehabilitation Sciences, 2023)
Background: Chronic ankle instability (CAI) is a common sports injury disease and characterized by limited mobility, perceived instability and muscle weakness, combined treatment of hip-knee-ankle is a common rehabilitation method. Tuina, as a traditional Chinese manual therapy, is usually used for CAI, but many of them only focus on the local ankle joint rather than the combination of hip and knee joint. Therefore, we have designed a randomized controlled trial (RCT) to investigate the effects of Tuina base on the concept of hip-knee-ankle conjugation on the stability and balance of lower limbs and ankle function in patients with CAI.We have designed a randomized controlled trial. A total of 72 participants with CAI will be randomly divided into functional training groups and hip-knee-ankle Tuina combined with functional training group in a 1:1 ratio. Participants in control group will receive 8 sessions of functional training (30min per session, twice a week for 4 weeks). Participants in intervention group will receive 8 sessions of Tuina combined with functional training (twice a week for 4 weeks). The primary outcomes include the Y-Balance Test (YBT) and Cumberland Ankle Instability Tool (CAIT). The Secondary outcomes include the Foot and Ankle Ability Measure (FAAM) and ankle range of motion (ROM). The outcome assessments will be conducted before the first intervention and after the last intervention.The aim of this study is to explore a safe and effective manipulation program and serve as reference for clinical treatment of CAI and expect to provide the necessary theoretical and practical support to our future research.